ANTIBACTERIAL SUSCEPTIBILITY IN URINARY TRACT INFECTION AMONG CHILDREN IN SULAIMANI - Hamawandi, Adnan M; Omer, Sherko A; Tayib, Tara Hussain (Journal of Sulaimani Medical College, 2015)
Background Urinary tract infection is a common infection among children with recognized pathogens that can have different susceptibility to antibacterial agents in different communities. It is recognized as a cause of acute morbidity and chronic medical conditions. Objectives The aim of this study was to identify the causative agents in pediatric urinary tract infection as well as the antimicrobial susceptibility of the isolated microorganisms. Patients and Methods A prospective study involved 86 pediatric patients suspected to have urinary tract infection. Physical examination and ultrasonographic examination were carried out. Urine samples were cultured, examined, and antimicrobial susceptibility was performed on bacterial isolates according to Kirby Bauer disk diffusion method. Results Pyuria was found in 60 (70 %) of the urine samples. Twenty nine (39%) samples yielded a positive culture while 31 (61%) of pyuria samples yielded no growth. Seven (19%) urine samples showed no pyuria but yielded a positive culture. The most frequently isolated bacteria were Escherichia coli followed by Proteus mirabilis, and Klebsiella pneumoniae. All E. coli isolates were susceptible to nitrofurantoin while 22 (95.6%) isolates out of 23 were susceptible to amikacin and 78% of E. coli were susceptible to ceftriaxone, cefixime and ciprofloxacin. E. coli isolates were highly resistant to cotrimoxazole and amoxicillin. Conclusion Pediatric urinary tract infections are more common in females than males in all age groups and affect more preschool age group. Common uropathogens were E. coli which were commonly resistant to many commonly used antibiotics such as cotrimoxazole and amoxicillin, but were highly sensitive to nitrofurantoin and amikacin.
Keywords: Urinary tract infection; Children; Antibacterial susceptibility; Sulaimani